What we'll burn last - Chavez, Heather (Mullholand Books/Little, Brown and Company, 2024)
When she was twelve, Leyna Clarke watched her older sister, Grace, walk away from their Sierra Nevada foothills home with her boyfriend, Adam Duran. Neither was ever seen again. Sixteen years later, a stranger who looks like Grace shows up at the restaurant where Leyna works--and vanishes soon after. When it comes out that Leyna was one of the last people to have talked with the young woman, Leyna's childhood crush Dominic, who is also Adam's brother, pleads with her to do the last thing she wants to do: come home. But Leyna isn't the only one who hasn't been able to leave that fateful night behind. Her mother, Meredith, still lives in the family's old home--even if she claims to believe the police's theory that Grace and Adam were willing runaways. Down the street, Adam and Dominic's mother Olivia has also stayed, determined to be there when her son finally returns...and to prove that Meredith and Leyna have been hiding something all these years. But the past isn't the only threat to the two families, or the missing girl. As a wildfire sparks, tempers flare and intentions turn deadly. Because someone in the neighborhood knows what really happened that night--and just how good the forest is at keeping its secrets.